Knockout of C1q/tumor necrosis factor-related protein-9 aggravates cardiac fibrosis in diabetic mice by regulating YAP-mediated autophagy - Ruan, Shiyan; Li, Jun; Lei, Shengyun; Zhang, Shaomeng; Xu, Dan; Zuo, Anju; Li, Linxi; Guo, Yuan (Frontiers in Pharmacology, 2024)
Introduction: Diabetic cardiomyopathy (DCM) is predominantly distinguished by impairment in ventricular function and myocardial fibrosis. Previous studies revealed the cardioprotective properties of C1q/tumor necrosis factor-related protein 9 (CTRP9). However, whether CTRP9 affects diabetic myocardial fibrosis and its underlying mechanisms remains unclear. Methods: We developed a type 1 diabetes (T1DM) model in CTRP9-KO mice via streptozotocin (STZ) induction to examine cardiac function, histopathology, fibrosis extent, Yes-associated protein (YAP) expression, and the expression of markers for autophagy such LC3-II and p62. Additionally, we analyzed the direct impact of CTRP9 on high glucose (HG)induced transdifferentiation, autophagic activity, and YAP protein levels in cardiac fibroblasts. Results: In diabetic mice, CTRP9 expression was decreased in the heart. The absence of CTRP9 aggravated cardiac dysfunction and fibrosis in mice with diabetes, alongside increased YAP expression and impaired autophagy. In vitro, HG induced the activation of myocardial fibroblasts, which demonstrated elevated cell proliferation, collagen production, and α-smooth muscle actin (α-SMA) expression. CTRP9 countered these adverse effects by restoring autophagy and reducing YAP protein levels in cardiac fibroblasts. Notably, the protective effect of CTRP9 was negated by inhibition of autophagy caused by chloroquine (CQ) or plasmid intervention with YAP overexpression. Discussion: Our findings suggest that CTRP9 can enhance cardiac function and mitigate cardiac remodeling in DCM through the regulation of YAP-mediated autophagy. CTRP9 holds promise as a potential candidate for pharmacotherapy in managing diabetic cardiac fibrosis.